Conversion to complete resection with mFOLFOX6 with bevacizumab or cetuximab based on K‐RAS status for unresectable colorectal liver metastasis (BECK study): Long‐term results of survival. (9th June 2020) - Okuno, Masayuki; Hatano, Etsuro; Toda, Rei; Nishino, Hiroto; Nakamura, Kojiro; Ishii, Takamichi; Seo, Satoru; Taura, Kojiro; Yasuchika, Kentaro; Yazawa, Takefumi; Zaima, Masazumi; Kanazawa, Akiyoshi; et al.
Abstract: Background/Purpose: To investigate the long‐term outcome and entire treatment course of patients with technically unresectable CRLM who underwent conversion hepatectomy and to examine factors associated with conversion to hepatectomy. Methods: Recurrence and survival data with long‐term follow‐up were analyzed in the cohort of a multi‐institutional phase II trial for technically unresectable colorectal liver metastases (the BECK study). Results: A total of 22/12 patients with K‐ RAS wild‐type/mutant tumors were treated with mFOLFOX6 + cetuximab/bevacizumab. The conversion R0/1 hepatectomy rate was significantly higher in left‐sided primary tumors than in right‐sided tumors (75.0% vs 30.0%, P  = .022). The median follow‐up was 72.6 months. The 5‐year overall survival (OS) rate in the entire cohort was 48.1%. In patients who underwent R0/1 hepatectomy (n = 21), the 5‐year RFS rate and OS rate were 19.1% and 66.3%, respectively. At the final follow‐up, seven patients had no evidence of disease, five were alive with disease, and 20 had died from their original cancer. All 16 patients who achieved 5‐year survival underwent conversion hepatectomy, and 11 of them underwent further resection for other recurrences (median: 2, range: 1‐4). Conclusions: Conversion hepatectomy achieved a similar long‐term survival to the results of previous studies in initially resectable patients, although many of them experienced several post‐hepatectomy recurrences. Left‐sided primary was found to be the predictor for conversion hepatectomy. Abstract : Highlight Okuno and colleagues report the final survival analysis of a multi‐institutional phase II trial for initially technically unresectable colorectal liver metastasis (BECK study). The 5‐year overall survival rate was 66.3% in patients who underwent conversion hepatectomy, which was the only independent prognostic factor for better overall survival on multivariate analysis.